Regulatory Effectiveness and the Empirical Impact of Variations in Regulatory Governance : Electricity Industry Capacity and Efficiency in Developing Countries - Cubbin, John; Stern, John (World Bank, Washington, DC, 2012)
The authors assess for 28 developing countries over the period 1980-2001 whether the existence of a regulatory law and higher quality regulatory governance are significantly associated with superior electricity outcomes. Their analysis draws on theoretical and empirical work on the impact of independent central banks and of developing country telecommunications regulators. The authors' empirical analysis concludes that a regulatory law and higher quality governance are positively and significantly associated with higher per capita generation capacity levels. In addition, this positive impact continues to increase for at least three years and probably for over 10 years as experience develops and regulatory reputation grows. The results are robust to alternative dynamic specifications and show no sign of any significant endogeneity